Boron-Doped Hydroxyapatite Coatings on NiTi Alloys Using the Electrophoretic Deposition Method: Enhanced Corrosion and Adhesion Performances - Aksoy, M. E.; Aksakal, B.; Aslan, N.; Dikici, B. (SPRINGER, 2021)
Metallic implants are functionalized with coatings due to the need to protect against biological corrosion in the body. Hydroxyapatite (HAp) has desirable biocompatibility and structural properties, but poor mechanical properties limit its use as a standalone coating. In this study, boron-doped hydroxyapatite (B-HAp) biocomposites containing 5, 10, and 15% boron by weight were synthesized by the sol-gel method and applied as a coating to NiTi using electrophoretic deposition (EPD). The deposition was carried out for 60, 90, and 120 s, and sintering at 750 degrees C for 75 minutes under vacuum. The coated substrates were then characterized by XRD, SEM, and FT-IR, and their adhesion strengths and in-vitro corrosion behaviors in simulated body fluid were compared with uncoated samples. The results showed that the microporous powders formed well-bonded structures, which positively affect adhesion strength. The highest adhesion strength (30 MPa) and corrosion resistance were achieved with 15 wt.% B-HAP coating at 120 s deposition time and 76.5 mu m coating thickness.
Keywords: bioceramic coating; boron; electrophoretic deposition; hydroxyapatite; NiTi; COMPOSITE; BEHAVIOR; IMPLANT; RESISTANCE; MORPHOLOGY; Materials Science